Analisis Keseragaman Citra pada Pesawat Ultrasonografi (USG) - Sudarsih, Kesawa; Setia Budi, Wahyu; Suryono, Suryono (BERKALA FISIKA, 2014)
The computer base system to determine uniformity of ultrasonography image quality has been developed at various attenuation(dB) and Time Gain Compensator (TGC).The equipment used in this study was 2-dimensional ultrasonic apparatus and multi-purpose multi-tissue phantom models 040GSE. Data collection was performed by scanning the phantom using a linear transducer with a frequency of 8 MHz. The mean and standard deviation of image density of it ROI calculated used computer base system then analyzed with trendline if the image density value in the range between mean and sd it means image uniform. The result shows that the uniformity of the image is influenced the value of attenuation and TGC. This value increase proportional with increasing attenuation. For greater value of the TGC the uniformity tends downward. At 45-60 dB obtained distribution image uniformity sd value is 0.20 and 0.28, and at minimum up to maximum TGC obtained distribution image uniformity sd value is 0.33 and 0.48. This value can be used for quality assurance reference of USG equipment. Keyword : USG Equipment, Uniformity, Region of Interest, Digital Image Processing